"The Boy Who Harnessed the Wind" Guide - Kansas State University, K-State First (Kansas State University, K-State First, 2020)
This guide provides resources for using the Kansas State University 2020 common book, “The Boy Who Harnessed the Wind” by William Kamkwamba and Bryan Mealer. Included in the guide are discussion questions, suggested classroom activities, other titles of interest, vocabulary, and additional resources.
Citation: K-State First (2020). The Boy Who Harnessed the Wind [Brochure]. Manhattan, Kansas: K-State First.
Keywords: Boy Who Harnessed the Wind, The; Common reading program; Guide; First-year experience program; Application of learning